The Heretic Saint: Guglielma of Bohemia, Milan, and Brunate - Newman, Barbara (Church History, 2005)
High above Lake Como in Lombardy, overlooking the cathedral city of Como and the southwestern branch of the lake, looms the tiny village of Brunate. It is a picturesque spot, beloved of mountain climbers, which enjoyed a brief heyday as a tourist mecca in the late nineteenth and early twentieth centuries. An efficient if ear-popping funicular railway, inaugurated in 1894, now scales the steep cliff in a brisk seven minutes. But in the Middle Ages, when most of our story is set, Brunate was as remote and inaccessible a site as one could hope to find. A hagiographer around 1600 described it as an “ignoble village on that mountain whose vast ridge towers above the city to the east.… The mountain is arduous and laborious to climb.” In 1578 the village had a mere 156 inhabitants, and as late as 1900 its year-round population was barely over 500.